2022
DOI: 10.5423/ppj.nt.08.2021.0130
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Rice Blast Disease at Yeoju of Korea in 2020

Abstract: Rice blast is the most destructive disease threatening stable rice production in rice-growing areas. Cultivation of disease-resistant rice cultivars is the most effective way to control rice blast disease. However, the rice blast resistance is easy to breakdown within years by blast fungus that continually changes to adapt to new cultivars. Therefore, it is important to continuously monitor the incidence of rice blast disease and race differentiation of rice blast fungus in fields. In 2020, a severe rice blast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…M. oryzae can cause rice blast, which poses a serious threat to rice yields worldwide [36,37]. As a result, natural products with a low toxicity to non-target organisms have attracted a widespread attention of researchers [38].…”
Section: Discussionmentioning
confidence: 99%
“…M. oryzae can cause rice blast, which poses a serious threat to rice yields worldwide [36,37]. As a result, natural products with a low toxicity to non-target organisms have attracted a widespread attention of researchers [38].…”
Section: Discussionmentioning
confidence: 99%
“…All samples were sequenced with a depth between 105X and 146X and a mean read length of >20kb (read N50 >30kb) ( Tables S4 and S5 ). Long reads were assembled into contigs and corrected using Flye (v2.9-b1768) [60], and polished with long reads using Medaka (v1.4.3) (https://github.com/nanoporetech/medaka). All assemblies were additionally polished using short read Illumina sequencing technologies (San Diego, USA) through two consecutive iterations of Pilon (v1.23) [61].…”
Section: Methodsmentioning
confidence: 99%
“…All samples were sequenced with a depth between 105X and 146X and a mean read length of >20kb (read N50 >30kb) (Tables S4 and S5). Long reads were assembled into contigs and corrected using Flye (v2.9-b1768) [60], and polished with long reads using Medaka (v1. and ERR9883756 (GE3) and ERR9866258 and ERR9866259 (GE16_2).…”
Section: Genome Sequencing and Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…Field observations showed irregular but severe occurrences of panicle blast depending on weather conditions from 1999 to 2008 (Lee et al 2010 ). Chung et al ( 2022 ) recently reported severe rice blast outbreaks occurred nationwide in 2020 in South Korea. Not only in South Korea, rice blast is also a major endemic yield reducer in rice production in North Korea, as inferred from many previous studies (Chen et al 2014 ; Chung et al 2019 ; Guo et al 2018 ; Kim 1999 ).…”
Section: Introductionmentioning
confidence: 99%